Simulation of nano carbon tube (NCT) in thermal interface material for electronic packaging application by using CFD software - Mazlan Mohamed; A.M. Mustafa Al Bakri; Razak Wahab; Zulhisyam Abdul Kari @ Abdullah; Muhammad Iqbal Ahmad; Mohd Hazim Mohamad Amini; Mohammad Amizi Ayob (2015)
This paper presents the nanocarbon tube in thermal interface material for electronic packaging application by using three dimensional numerical analysis of heat and fluid flow in computer. 3D model of electronic packaging is built using GAMBIT and simulated using FLUENT software. The study was made for a microprocessors arranged in line under different types of inlet velocities and package (chip) powers. The results are presented in terms of average junction temperature when chip powers have been increased from 2 W to 5 W. The junction temperature is been observed and it was found that the junction temperature of the electronic packaging using nanocarbon was able to wind stand the increasing in chip power from 2 W until 5 W. It also found that the material selection play important roles to control and manage the junction temperature. The strength of CFD software in handling heat transfer problems is proved to be excellent.